2009
DOI: 10.1292/jvms.71.879
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Enzyme Immunoassay for Urinary Pregnanediol-3-Glucuronide in a Female Giant Panda (Ailuropoda melanoleuca)

Abstract: In order to enable monitoring of the reproductive status of the female giant panda after observation of estrus behavior, we developed an enzyme immunoassay (EIA) system for urinary pregnanediol-3-glucuronide (PdG), a progesterone metabolite, using commercial reagents and examined the changes in the urinary concentration of PdG in a female giant panda that showed pseudopregnancy and suspicious pseudopregnancy in 6 consecutive years. The developed EIA system had good reproducibility (intra-and interassay CVs 6.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Urine concentrations of E 1 G and PdG were assayed using an enzyme immunoassay using the same methods and reagents as described by Hama et al . The polyclonal E 1 G antiserum (FKA‐224E; Cosmo Bio Co., Ltd., Tokyo, Japan) was raised in rabbits against estrone‐3‐glucuronide‐BSA and subsequently cross‐reacted with 100% estrone, 170% E 1 G, 25% estrone‐3‐sulfate, 1% estradiol, 0.1% estriol, 1.2% estradiol‐3‐glucuronide, 0.1% estradiol‐3‐sulfate, 0.05% testosterone, 0.07% 4‐androstenediol, 0% progesterone, 0% cortisol, and 0% 17‐α‐OH‐progesterone.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Urine concentrations of E 1 G and PdG were assayed using an enzyme immunoassay using the same methods and reagents as described by Hama et al . The polyclonal E 1 G antiserum (FKA‐224E; Cosmo Bio Co., Ltd., Tokyo, Japan) was raised in rabbits against estrone‐3‐glucuronide‐BSA and subsequently cross‐reacted with 100% estrone, 170% E 1 G, 25% estrone‐3‐sulfate, 1% estradiol, 0.1% estriol, 1.2% estradiol‐3‐glucuronide, 0.1% estradiol‐3‐sulfate, 0.05% testosterone, 0.07% 4‐androstenediol, 0% progesterone, 0% cortisol, and 0% 17‐α‐OH‐progesterone.…”
Section: Methodsmentioning
confidence: 99%
“…Urine creatinine concentrations were measured using the same methods and reagents described by Hama et al . The concentrations of steroid hormones and protease were calculated as ng or μg/mg of creatinine (Crmg).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Marker a4 showed higher signal intensities in women than in men and was putatively annotated as pregnanediol-3-glucuronide or 3a,20a-dihydroxy-5b-pregnane 3-glucuronide, natural human metabolites of pregnanediol or 3a,20a-dihydroxy-5b-pregnane, respectively, and generated in the liver by UDP glucuronyltransferase (HMDB description, http://www.hmdb.ca/ metabolites/HMDB10318 and http://www.hmdb.ca/metabolites/HMDB10352), or isomers. Pregnanediol-3-glucuronide is a metabolite of progesterone present in large amounts in the urine of pregnant animals 18 and has long been proposed in the scientific literature to help identify the ovulatory period. 19 Pregnanediol, pregnanedione and pregnanolone are products of the pathway along which progesterone is primarily metabolized.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used genetic methods to extract phylogenetic and heterogeneous information on the giant panda (Pagés et al, 2008;Hama et al, 2009;Hao et al, 2009). Research has shown that the karyotype of the giant panda is similar to that of the bear (Nash et al, 1998), suggesting that the bear and the giant panda have similar genome sizes.…”
Section: Introductionmentioning
confidence: 99%